On ground validation of debris removal technologies. (May 2019) - Colmenarejo, P.; Graziano, M.; Novelli, G.; Mora, D.; Serra, P.; Tomassini, A.; Seweryn, K.; Prisco, G.; Fernandez, J. Gil
Abstract: The goal of the activity On-ground Validation of Debris Removal Technologies, ORCO, has been to investigate and mature the complex couplings between the different control systems (GNC including image processing and robotics) for autonomous rigid capture between an active chaser vehicle and a cooperative/non-cooperative target, and derive the required algorithms and perform a HW-in-the-loop end-to-end demonstration. The prototyped solution is tested in the most realistic conditions obtainable on ground, including also the dynamics of the system as well as the relative visual based navigation system. The on-ground validation and integration is performed taking advantage of the GMV platform-art © dynamic test facility located in Madrid, Spain, with the addition of the hardware provided by the partners: robotic system from CBK (Poland) and visual system from TSD (Italy). Highlights: Critical On-Orbit Servicing/Active Debris Removal technologies considerably matured. Onground E2E proof of OOS/ADR chain in the full operations sequence MIL, SIL-PIL, HIL. RVD and close-proximity operations demonstrated with vision-based relative nav sensor. Independent operation of chaser GNC and robotic manipulator controller demonstrated. Achieved TLR 4/5 for the full system and 5/6 for the vision-based system.